Cyc‐DEP: Cyclic immunofluorescence profiling of particles collected using dielectrophoresis. Issue 16 (11th July 2022) - Gustafson, Kyle T.; Sayar, Zeynep; Le, Hillary; Gustafson, Steven L.; Gower, Austin; Modestino, Augusta; Ibsen, Stuart; Heller, Michael J.; Esener, Sadik; Eksi, Sebnem E.
Abstract: Cancer is a highly heterogenous disease that requires precise detection tools and active surveillance methods. Liquid biopsy assays provide an agnostic way to follow the complex trajectory of cancer, providing better patient stratification tools for optimized treatment. Here, we present the development of a low‐volume liquid biopsy assay called cyc‐DEP (cyclic immunofluorescent imaging on dielectrophoretic chip) to profile biomarkers collected on a dielectrophoretic microfluidic chip platform. To enable on‐chip cyclic imaging, we optimized a fluorophore quenching method and sequential rounds of on‐chip staining with fluorescently conjugated primary antibodies. cyc‐DEP allows for the quantification of a multiplex array of proteins using 25 µl of a patient plasma sample. We utilized nanoparticles from a prostate adenocarcinoma (LNCaP) cell line and a panel of six target proteins to develop our proof‐of‐concept technique. We then used cyc‐DEP to quantify blood plasma levels of target proteins from healthy individuals, low‐grade and high‐grade prostate cancer patients ( n  = 3 each) in order to demonstrate that our platform is suitable for liquid biopsy analysis in its present form. To ensure accurate quantification of signal intensities and comparisons between different samples, we incorporated a signal intensity normalization method (fluorescent beads) and a custom signal intensity quantification algorithm that account for the distribution of signal across hundreds of collection regions on each chip. Our technique enabled a threefold improvement in multiplicity for detecting proteins associated with fluid samples, opening doors for early detection, and active surveillance through quantification of a multiplex array of biomarkers from low‐volume liquid biopsies.